2016
DOI: 10.1103/physrevfluids.1.064402
|View full text |Cite
|
Sign up to set email alerts
|

Smooth- and rough-wall boundary layer structure from high spatial range particle image velocimetry

Abstract: Two particle image velocimetry arrangements are used to make true spatial comparisons between smooth-and rough-wall boundary layers at high Reynolds numbers across a very wide range of streamwise scales. Together, the arrangements resolve scales ranging from motions on the order of the Kolmogorov microscale to those longer than twice the boundary layer thickness. The rough-wall experiments were obtained above a continuous sandpaper sheet, identical to that used by Squire et al. [J. Fluid Mech. 795, 210 (2016)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 74 publications
1
19
3
Order By: Relevance
“…Unfortunately, the present PIV measurements are incapable of resolving either of the regions described above, due to their limited streamwise extent and to laser reflection issues near to the wall (see Squire et al 2016b). This is demonstrated by the dashed box in figure 1(a), which shows the range of wall-normal locations and streamwise scales fully resolved by the PIV measurements.…”
Section: Spectra Of Streamwise Velocity Fluctuationsmentioning
confidence: 88%
See 3 more Smart Citations
“…Unfortunately, the present PIV measurements are incapable of resolving either of the regions described above, due to their limited streamwise extent and to laser reflection issues near to the wall (see Squire et al 2016b). This is demonstrated by the dashed box in figure 1(a), which shows the range of wall-normal locations and streamwise scales fully resolved by the PIV measurements.…”
Section: Spectra Of Streamwise Velocity Fluctuationsmentioning
confidence: 88%
“…Note that T = TU ∞ /δ × 10 −3 , where T is the sampling time. T14, MW16 and S16b are abbreviations for Talluru et al (2014a), Morrill-Winter et al (2016) and Squire et al (2016b), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2011; Vallikivi, Ganapathisubramani & Smits 2015; Squire et al. 2016). Further investigations revealed that the VLSM carry more than 50 % of the turbulent kinetic energy (TKE) (Balakumar & Adrian 2007) and have a significant amplitude modulation effect on the small-scale motions near the wall (Hutchins & Marusic 2007 b ; Mathis et al.…”
Section: Introductionmentioning
confidence: 99%